THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN THE TEACHING OF THE SCIENCE OF THE BASICS OF NURSING - Xusainova Muxiba Shavkatovna; Kafiyeva Martaba Xushvaqtovna; Hakimova Xonbuvi (Web of Journals Publishing, 2024)
This article explores the significance of modern pedagogical technologies in the teaching of the fundamentals of nursing science. It delves into the literature to analyze existing research on this topic, investigates various methods employed, presents results, engages in discussion, and draws conclusions with suggestions for future directions in nursing education.
Keywords: Nursing education, pedagogical technologies, science of nursing basics, modern teaching methods, literature analysis, results, discussion, conclusions, suggestions.